REPORTING DISCLOSURE LEVELS AND COMPLIANCE WITH BB, AAOIFI, B/IFRS AND SEC OF ISLAMIC FINANCIAL INSTITUTIONS IN BANGLADESH - Islam, Md Robiul; Sadekin, Mohammad Shamsus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Compliance with financial reporting guidelines/standards promulgated by Regulatory Bodies has become a crucial issue of the day after a series of corporate debacles over a few years. Regulators, professional bodies and researchers throughout the world have expressed their concern about the need for improved accounting pronouncements and compliance for providing better information than previously required for the preparation and presentation of corporate financial reporting. The present study primarily focuses on the reporting disclosure levels and compliance with Bangladesh Bank (BB) Guidelines, Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) Accounting Standard, Bangladesh/International Financial Reporting Standard (B/IFRS) and Securities and Exchange Commission (SEC) Rules of Islamic Financial Institutions in Bangladesh. Annual reports of (08) eight Islamic banks in Bangladesh have been examined for the year ending 2015. The results showed that the Islamic banks significantly followed the selected accounting guidelines/standards under review and did bring remarkable changes in the financial reporting practices made by the Islamic banks in Bangladesh. The study attempted to examine empirically the levels of disclosure in corporate annual reports of Islamic banks in Bangladesh. The study recommended increasing the level of compliance to make their financial reports more informative. The study also tries to ascertain the regulatory necessary requirements in preparing the financial statements of banks under Islamic shariah and tries to display the compliance status of these banks with legislations. The average compliance rate is 93.28% for BB guidelines, 46.54% for AAOIFI Accounting Standard, 48.50% for B/IFRS and 51.99% for SEC rules considering all required aspects of financial reports. Compiling all of the requirements regarding financial reports of regulatory bodies will be helpful for banks to make financial reports convenient.